2018
DOI: 10.1016/j.neuint.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the branched-chain α-ketoacid dehydrogenase complex E1α subunit and glutamate dehydrogenase in the human brain and their role in neuro-metabolism

Abstract: Glutamate is the major excitatory neurotransmitter of the central nervous system, with the branched-chain amino acids (BCAAs) acting as key nitrogen donors for de novo glutamate synthesis. Despite the importance of these major metabolites, their metabolic pathway in the human brain is still not well characterised. The metabolic pathways that influence the metabolism of BCAAs have been well characterised in rat models. However, the expression of key proteins such as the branched-chain α-ketoacid dehydrogenase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…Physiological importance of the brain metabolism of glutamate after SCI is supported by the most significant and strongest correlation of the cortex glutamate level with the BBB score, added by the positive correlation trend of BBB with the glutamate-generated GABA. The trends of positive correlations of BBB score with the branched chain amino acids leucine and isoleucine agree with the known role of these amino acids in supporting both the TCA cycle flux at insufficient OGDHC function (Santos et al, 2006;Trofimova et al, 2012) and the glutamate homeostasis during the neurotransmission (Yudkoff, 2017;Hull et al, 2018).…”
Section: Metabolic Markers and Physiological Significance Of The Longsupporting
confidence: 78%
“…Physiological importance of the brain metabolism of glutamate after SCI is supported by the most significant and strongest correlation of the cortex glutamate level with the BBB score, added by the positive correlation trend of BBB with the glutamate-generated GABA. The trends of positive correlations of BBB score with the branched chain amino acids leucine and isoleucine agree with the known role of these amino acids in supporting both the TCA cycle flux at insufficient OGDHC function (Santos et al, 2006;Trofimova et al, 2012) and the glutamate homeostasis during the neurotransmission (Yudkoff, 2017;Hull et al, 2018).…”
Section: Metabolic Markers and Physiological Significance Of The Longsupporting
confidence: 78%
“…Until the study by Helms et al (2012), the potential for Glu metabolism within endothelial cells was not considered. Our group have shown that GDH and the BCKD complex are also expressed in endothelial cells, indicating that Glu oxidation can occur and will dependent on concentration and cellular redox state (Hull et al 2018). The role of BCATm in endothelial cells has yet to be confirmed but most likely will be important in regulating brain glutamate through metabolism through the BCATm/ BCKD/GDH metabolon or additional cellular roles yet to be defined.…”
Section: Cellular Distribution Of Branched Chain Aminotransferasesmentioning
confidence: 98%
“…The tissue distribution of total BCKDH activity in humans was reported to be 164.5 6 18 mU per gram wet weight, with kidneys showing the highest total activity, small intestine the lowest, and undetectable activity in the pancreas (22). BCKDH is most active in the liver and brain and shows about half as much activity in the kidney and heart (2, 3) ( Table 2), with the E1-a subunit located in the neurons as well as in the endothelial cells throughout the brain vasculature (24). Unlike BCAT, BCKDH activity is significantly low in resting skeletal muscle (2), with the majority of the enzyme complex residing in its inactive, phosphorylated state (33).…”
Section: Bckdhmentioning
confidence: 99%
“…Notably, BCAA oxidation is significantly less than BCAA transamination, suggesting efficient amino group transfer from BCAAs to generate alanine and glutamine, important gluconeogenic substrates in the liver and kidney, respectively (23). In the human neurons, BCATm forms a complex with the BCKA dehydrogenase (BCKDH) E1-a subunit and glutamate dehydrogenase 1 (GDH1) (24), resulting in a 12-fold increase in BCKA decarboxylation (24). GDH1 protein subsequently binds to the pyridoxamine-59-phosphate form of BCATm, thus replenishing the a-ketoglutarate (24).…”
Section: Bcatmentioning
confidence: 99%